Arab Republic of Egypt : Detailed Assessment Report on Anti-Money Laundering and Combatting the Financing of Terrorism - World Bank (Washington, DC, 2013)
This assessment of the anti-money laundering (AML) and combating the financing of terrorism (CFT) regime of the Arab Republic of Egypt (Egypt) is based on the Forty Recommendations 2003 and the Nine Special Recommendations on Terrorist Financing 2001 of the Financial Action Task Force (FATF), andwas prepared using the AML/CFT assessment Methodology 2004, as updated in February 2008. The assessment team considered all the materials supplied by the authorities, the information obtained on site during their mission from 12 to 26 October 2008, and other verifiable information subsequently provided by the authorities. During the mission, the assessment team met with officials and representatives of all relevant government agencies and the private sector. A list of the bodies met is set out in Annex 1 to the detailed assessment report. The assessment was conducted by a team of assessors composed of staff of the World Bank and two experts acting under the supervision of the World Bank. The evaluation team consisted of: Latifah Merican Cheong (Team leader); Cedric Mousset (co-team leader and financial expert), Stuart Yikona (legal expert); and Isaku Endo (financial expert), all from the Financial Market Integrity unit (FPDFI) and Horst Intscher (FIU expert, Consultant) and Younus Almoalem, (Law enforcement expert, Consultant). The assessors reviewed the institutional framework, the relevant AML/CFT laws, regulations, guidelines and other requirements, and the regulatory and other systems in place to deter and punish money laundering (ML) and the financing of terrorism (FT) through financial institutions and Designated Non-Financial Businesses and Professions (DNFBP). The assessors also examined the capacity, implementation, and effectiveness of all these systems. This report provides a summary of the AML/CFT measures in place in Egypt at the time of the mission or shortly thereafter. It describes and analyzes those measures, sets out Egypt s levels of compliance withthe FATF 40+9 Recommendations (see Table 1) and provides recommendations on how certain aspects of the system could be strengthened (see Table 2). The report was produced by the World Bank as part of the Financial Sector Assessment Program (FSAP) of Egypt. It was also presented to the MENA FATFand endorsed by this organization at its plenary meeting in Bahrain on 19 May 2009.